ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SISTEM INFORMASI AKUNTANSI KEUANGAN DI DESA KECAMATAN PORTIBI KABUPATEN PADANG LAWAS UTARA - asnita khoiriyah (Jurakunman (Jurnal Akuntansi dan Manajemen), 2023)
This study aims to examine what factors influence the use of Financial Accounting Information Systems (AIS). In the village of Portibi District, North Padang Lawas Regency, the problems that occur are not yet optimal in using the use of village financial accounting information systems because the system is always changing, which causes the use of accounting information systems to be integrated and computerized. The research design is quantitative research. The sample in this study was the village head, village secretary, financial officer in each village, Portibi sub-district, and accounting department. The sampling technique used the purposive sampling method, namely taking samples from the population based on certain criteria with 108 respondents. The data source used in this study was primary data with research instruments in the form of questionnaires. The collected data was then analyzed using multiple linear regression analysis techniques. Regarding User Involvement (0.187), it is greater than the 5% alpha (0.05) or the ttable value (1.65922) (n-k=108-5=103), so it is concluded that the Factors Affecting the Financial Accounting Information System in the Portibi District Village North Padang Lawas Regency has a significant effect, while the variable based on the partial test (t test) has a significant value of 0.017 which is greater than the 5% alpha (0.05) or the ttable value (1.65922) (n-k=108-5=103) So it can be concluded that regarding The Personal Engineering program on the financial accounting information system in the Portibi sub-district, North Padang Lawas Regency did not have a significant effect.